Proteomic profiling of the Macrobrachium rosenbergii nodavirus infection: A study of early to late-stage infection in vitro - Chen, Ken Fong; Tan, Wen Siang; Ong, Lin Kooi; Zainal Abidin, Syafiq Asnawi; Othman, Iekhsan; Tey, Beng Ti; Lee, Ronald Fook Seng (Elsevier B.V., 2024)
The Macrobrachium rosenbergii nodavirus (MrNV), belonging to the Nodaviridae family, is responsible for a deadly infection in freshwater prawns, especially impacting the post-larvae of Macrobrachium rosenbergii with a mortality rate reaching 100 %. Recent research has shed light on the typical process of MrNV trafficking within the host, illustrating how the virus navigates through cells as the infection advances and the subsequent cellular alterations. Yet, the specific cellular pathways disrupted by MrNV, leading to these alterations, are underexplored. Furthermore, the precise effects of the MrNV capsid protein, known for its strong immune response, on the host cells are not well understood. This study seeks to clarify these impacts by analysing and comparing the protein expression profiles in healthy, MrNV virus-like particle (VLP) invaded, and MrNV-infected Sf9 cells over a 24-h period using a mass spectrometry based proteomics approach. Our findings show that the protein expression in MrNV VLP-invaded and MrNV-infected Sf9 cells during the mid-infection stages is similar, involving key signalling pathways like the eukaryotic translation system, cell cycle, actin cytoskeleton regulation, and the mTOR pathway. However, changes in protein expression for key proteins such as 40S and 60S ribosomal subunits, 14–3-3 protein epsilon, and tubulin beta chain persisted only within the MrNV-infection group whilst the protein expression in the VLP-invasion group reverted to baseline levels over time, underscoring the transient nature of VLP effects due to their inability to replicate. Additionally, a reduction in peroxiredoxin levels was observed in the later stages of MrNV infection, indicating a potential viral strategy to trigger apoptosis and release virions. Our results suggest that MrNV increases expression of 40S ribosome activity to boost viral protein synthesis while suppressing 60S ribosome expression, which impedes the synthesis of host proteins. MrNV also appears to extend the lifespan of host cells by interfering with their cell cycle and blocking apoptotic pathways, thus facilitating viral replication. This research enhances our comprehension of MrNV's infectious mechanism, delineates the pathways exploited by the virus, and identifies crucial molecular targets for potential therapeutic intervention.